Transnational Entrepreneurship & Ghanaians Abroad: What are the Motives? A Case Study in Europe and United States of America. - Asiedu, Elvis (International Journal of Social Sciences and Management, 2017)
Using data collected from Ghanaians living in the United Kingdom, and the USA; this research examined the motives that drive the performance of transnational entrepreneurship, the mobility involves and why such businesses normally fail. The study was conducted in 2013-2017; with a population size of 120 Ghanaians living in the UK and the USA. The objective was to find out what really drives the performance of these entrepreneurs who operate in a condition where costs may be known but rewards are uncertain, yet they are motivated. The research employed both deductive and exploratory approach and the methods were both primary and secondary. The study focused on small-scale entrepreneurs who run their businesses through personal social connections. The general results show that though individuals motives for seeking self-employment are diverse and numerous; and differ on certain points. However, there are some basic motives common to all and that is majority of the respondents with the average score of 63.3% supported that Economic Mobility, Financial Independence, Success Perspective, and Social Factors, are the most driven factors for the engagement in transnational entrepreneurship. We discovered that in a small-scale business, where most often do not have the needed managerial capabilities to engage in corporation, trust can be used to avoid loses that might come as a result of someone’s misconduct. We also discovered that the successes of these entrepreneurs are based on attitudinal; the degree of embededdness in the home country; personal and the institutional regulations of the destination countries. The results found that Ghana Transnational Entrepreneurs (GTE) are more into Merchandising Business with (59.21%) as compared to Service Business (34.21%) and Manufacturing Business (10.53%); and such businesses are managed and run mostly by their families (59.21%). Ashanti Region of Ghana was spotted to be more involved in doing business with 52.63%. Int. J. Soc. Sc. Manage. Vol. 4, Issue-3: 210-222